ANALISA PEMANFAATAN M-COMMERCE UNTUK MENINGKATKAN KUNGGULAN BERSAING DI ERA INTERNET MOBILE MENGGUNAKAN METODE FIVE-FORCE MODEL (Studi Kasus Tokopedia.com) - Susiyanto, hendro (Universitas Krisnadwipayana, 2024)
Since two decades, technology analysts predicted that mobile technology is the future, about how we conductbusiness in the era of a mobile internet. Analysts argue that mobile technology will be the backbone of electroniccommerce (e-commerce) and will change the economic environment to such an extent that